2001
DOI: 10.1109/4233.966105
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-based space-frequency compression of ultrasound images

Abstract: Abstract-This paper describes the compression of grayscale medical ultrasound images using a recent compression technique, i.e., space-frequency segmentation (SFS). This method finds the rate-distortion optimal representation of an image from a large set of possible space-frequency partitions and quantizer combinations and is especially effective when the images to code are statistically inhomogeneous, which is the case for medical ultrasound images. We implemented a compression application based on this metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…One study concluded that wavelet-based methods such as SPIHT are subjectively superior to JPEG compressed at a moderately high bit-rate (Chiu et al, 2001). However, SPIHT developed ringing artifacts at compression rates above 12:1, impacting diagnostic acceptability.…”
Section: Thresholdingmentioning
confidence: 99%
“…One study concluded that wavelet-based methods such as SPIHT are subjectively superior to JPEG compressed at a moderately high bit-rate (Chiu et al, 2001). However, SPIHT developed ringing artifacts at compression rates above 12:1, impacting diagnostic acceptability.…”
Section: Thresholdingmentioning
confidence: 99%
“…Unfortunately since some of these authors did not mention image size and pixel depth, it is difficult to make direct comparisons. Chiu et al 17 compressed US images using the modified wavelet technique. They used a US image size of 640 × 480 × 8 as has been used in this study.…”
Section: Acceptable Compression Ratiomentioning
confidence: 99%
“…Recently, the subband or wavelet coding has proven to be a very useful framework for loss compression of medical images (Gupta, N., Swamy, M.N.S., & Plotkin, E., 2005;Chiu, E., Vaisey, J., & Atkins, S. 2001;Li, X., Hu, G., & Gao, S., 1999).…”
Section: Introductionmentioning
confidence: 99%